1996
DOI: 10.1021/ma9605964
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Helix−Helix Transition of Poly(β-phenylpropyl l-aspartate) Involving a Screw-Sense Inversion in the Solid State

Abstract: Poly(β-phenylpropyl l-aspartate) exhibits a novel helix−helix transition in the solid state at around 160 °C. The transition takes place reversibly in a narrow temperature range during a heating and cooling cycle, indicating that it is essentially of a first order. A combined use of circular dichroism, X-ray, and 13C CP/MAS NMR measurements revealed that the transition is due to an interconversion of the helical screw sense from a right-handed α-helix to a left-handed helix. An unwinding and rewinding of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
66
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 28 publications
(56 reference statements)
3
66
1
Order By: Relevance
“…Recently, a number of artificial helical polymers bearing enantiomerically pure chiral or achiral bulky functional side groups have been successfully prepared by the precisely controlled polymerization of functional monomers with well‐defined catalysts 27–35. These synthetic helical polymers exhibit many interesting characteristics, including electronic and photophysical properties,21, 36 the formation of thermotropic liquid crystals,37, 38 chiral and chirality recognition ability,39–51 and helix–helix transition 48, 52–61. Therefore, understanding the relationship between the functions and the global structures and local conformations is crucial in this field 27–35.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of artificial helical polymers bearing enantiomerically pure chiral or achiral bulky functional side groups have been successfully prepared by the precisely controlled polymerization of functional monomers with well‐defined catalysts 27–35. These synthetic helical polymers exhibit many interesting characteristics, including electronic and photophysical properties,21, 36 the formation of thermotropic liquid crystals,37, 38 chiral and chirality recognition ability,39–51 and helix–helix transition 48, 52–61. Therefore, understanding the relationship between the functions and the global structures and local conformations is crucial in this field 27–35.…”
Section: Introductionmentioning
confidence: 99%
“…The πL‐helix of PPLA was concluded to be the 4.25 16 helix with a unit height of 1.17 Å which is slightly larger than 1.15 Å of the 4.4 16 helix of Low et al The helical characteristics of the π‐helix are significantly different from those of ω‐helix (4.0 13 helix). Watanabe et al found that polyaspartates bearing longer side chains such as phenylpropyl, phenylbutyl, and phenylpentyl undergo thermally reversible screw‐sense inversion (from αR‐helix to left‐handed ω‐helix (ωL‐helix)) in the solid state . Watanabe et al reported that the unit heights of ωL‐helices (4.0 13 ) obtained by the X‐ray diffraction studies were 1.27 ~ 1.33 Å, much smaller than that (1.5 Å) of the αR‐helix (3.6 13 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Watanabe et al found that polyaspartates bearing longer side chains such as phenylpropyl, phenylbutyl, and phenylpentyl undergo thermally reversible screw‐sense inversion (from αR‐helix to left‐handed ω‐helix (ωL‐helix)) in the solid state . Watanabe et al reported that the unit heights of ωL‐helices (4.0 13 ) obtained by the X‐ray diffraction studies were 1.27 ~ 1.33 Å, much smaller than that (1.5 Å) of the αR‐helix (3.6 13 ) . Furthermore, it has been observed that PPLA exhibits thermally induced helix‐sense inversion in its dilute solutions or in the lyotropic liquid crystalline state .…”
Section: Introductionmentioning
confidence: 99%
“…Biological and synthetic polymers often exhibit conformational transitions between ordered (e.g., helix and rod) and disordered (coil and globule) states by external stimuli such as the temperature,1–3 solvent,4–6 molecular weight,7, 8 pH,9, 10 and light 11, 12. However, examples of helix ( P , right‐handed) to‐helix ( M , left‐handed) transitions in synthetic helical polymers are rare and restricted to specially designed polymers, such as polyacetylenes,13–16 polyisocyanates,17–23 polypeptides,24–26 polythiophenes,27–29 poly(triarylmethyl methacrylate),30 poly( N ‐propargylamides),31 and polysilanes 32–37. Such materials with chiroptical switching properties may be potential candidates for optical devices, data storage, and liquid‐crystal displays 38, 39…”
Section: Introductionmentioning
confidence: 99%